CdS/ZnS core–shell nanocrystal photosensitizers for visible to UV upconversion. Issue 8 (7th June 2017) - Gray, Victor; Xia, Pan; Huang, Zhiyuan; Moses, Emily; Fast, Alexander; Fishman, Dmitry A.; Vullev, Valentine I.; Abrahamsson, Maria; Moth-Poulsen, Kasper; Lee Tang, Ming
Abstract : Herein we report the first example of nanocrystal (NC) sensitized triplet–triplet annihilation based photon upconversion from the visible to ultraviolet (vis-to-UV). Abstract : Herein we report the first example of nanocrystal (NC) sensitized triplet–triplet annihilation based photon upconversion from the visible to ultraviolet (vis-to-UV). Many photocatalyzed reactions, such as water splitting, require UV photons in order to function efficiently. Upconversion is one possible means of extending the usable range of photons into the visible. Vis-to-UV upconversion is achieved with CdS/ZnS core–shell NCs as the sensitizer and 2, 5-diphenyloxazole (PPO) as annihilator and emitter. The ZnS shell was crucial in order to achieve any appreciable upconversion. From time resolved photoluminescence and transient absorption measurements we conclude that the ZnS shell affects the NC and triplet energy transfer (TET) from NC to PPO in two distinct ways. Upon ZnS growth the surface traps are passivated thus increasing the TET. The shell, however, also acts as a tunneling barrier for TET, reducing the efficiency. This leads to an optimal shell thickness where the upconversion quantum yield ( Φ ′UC ) is maximized. Here the maximum Φ ′UC was determined to be 5.2 ± 0.5% for 4 monolayers of ZnS shell on CdS NCs.